2016
DOI: 10.2147/ieh.s56239
|View full text |Cite
|
Sign up to set email alerts
|

Combating the threat of stem cell tourism through patient education and government regulation

Abstract: Advances in stem cell research and media publicity of stem cell potential have raised the hopes of patients with severe disabilities and conditions which lack a cure. While stem-cell-based therapies are the clinical standard of care for a few hematological conditions, stem cell tourism continues to rise worldwide. This rise is driven in part by patients' need for alternative treatment for difficult conditions and increased online access to health information. Unfortunately, clinics around the world are exploit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…These factors both benefit for wound healing [14,15]. However, it was found that eight of nine late-passage human embryonic stem cell (hESC) lines had one or more genomic alterations commonly observed in human cancers [16,17]. The secure application of stem cells in tissue engineering should be seriously taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…These factors both benefit for wound healing [14,15]. However, it was found that eight of nine late-passage human embryonic stem cell (hESC) lines had one or more genomic alterations commonly observed in human cancers [16,17]. The secure application of stem cells in tissue engineering should be seriously taken into account.…”
Section: Introductionmentioning
confidence: 99%